in vitro evaluation of inhibitory activity of enteric Bifidobacterium isolates against Shiga toxin producing E.coli (STEC)O157:H7 - M. Alrekaby, Samar; A. Alwendawi, Shadan (Iraqi Journal of Science, 2023)
Six Bifidobacterium isolates, isolated from breast – feed infant faces on reduced de Man Rogosa and Sharp medium (MRS - C). Isolates identified to species level on the basis of : microscopical properties, biochemical tests, fructose-6-phosphate phosphoketolase enzyme(F6PPK) activity and carbohydrates fermentation profile. Results showed that B. adolescentis was the predominant species (B4,B5and B6),the other species were B. breve(B3),B. longum (B1), B. dentium(B2).Strains were screened for their inhibitory effects against pathogenic bacteria shiga toxin producing E.coli(STEC)O157:H7 using agar – well diffusion method.B3 and B6 showed clear inhibitory actions toward STEC,22 mm and 15 mm diameter of inhibition zone srespectively. While the rest of isolates did not pronouncedany inhibitory activities. This indicate that the efficiency of probiotic bacterial strain specially Bifidobacterium spp. as antibacterial factor to treat or reduce bloody diarrhea and hemorrhagic urinary syndrome (HUS) as symptom of (STEC) infection .